Impact of task variation and microbreaks on muscle fatigue at seated and standing postures. - Loh, Ping Yeap; Choi, Jeewon; Lin, Yu (Work, 2023)
BACKGROUND: Prolonged and sustained work posture among computer users is one of the main factors that contributes to musculoskeletal discomfort. Rest-break interventions such as task variation and microbreaks may help prevent muscle fatigue and work-related musculoskeletal disorder. OBJECTIVE: We aimed to investigate the effects of task variation and microbreaks at seated and standing workstations on forearm muscle activity, namely extensor digitorum communis, extensor carpi ulnaris, flexor digitorum superficialis, and flexor carpi ulnaris; mouse operation force (vertical compression force); mouse operation parameters; and perceived body discomfort during mouse operation. METHODS: Twelve healthy right-handed young adults were recruited (male: n = 7, 21.6±1.4 years; female: n = 5, 21.4±1.7 years). Participants performed three blocks of computer tasks (computer mouse operation and typing) in both seated and standing postures with each block lasting for 30 min. Surface electromyography (EMG) of the forearm muscles and operation force were monitored during computer mouse operation. Body discomfort rating was recorded at the end of each block. RESULTS: With simulated task variation and microbreaks, work posture and work time showed no significant difference with EMG amplitude and mouse operation force. CONCLUSION: Task variation and microbreaks could be of benefit to computer users by reducing muscle fatigue during long hours of computer work at both seated and standing workstations.